Vascular Calcification and Subendocardial Ischemia in Hemodialysis Patients: A New Morpho-Functional Score to Assess Cardiovascular Risk: the Solofra Score - L. Sirico, Maria; Di Micco, Lucia; De Blasio, Antonella; Di Iorio, Biagio (Current Hypertension Reviews, 2014)
Background: ESRD (end-stage renal disease) patients have a high cardiovascular mortality risk. A morphofunctional approach of vascular calcifications and myocardial perfusion is needed for the management of ESRD patients. We used SEVR (sub-endocardial viability ratio) and Kauppila score from the dialysis population of the Independent study to create a new morpho-functional score to assess cardiovascular risk in this population (the Solofra score). Materials and Methods: 184 patients were followed-up for 36 months. A side lumbar X-ray was performed to assess vascular calcifications of lumbar aorta using the Kauppila score. Central aortic pressure and pulse velocity wave (PWV) were assessed at the carotid artery site. Myocardial perfusion was estimated with SEVR. Independent risk mortality factors were identified with univariate regression analysis (p<0.01); significance was defined as p<0.05. Results: Kauppila score was 13±10(range 0-24); PWV was 9.5±4 m/sec; basal SEVR was 1.3±0.9. We observed an improvement of ROC curves for SEVR and Kauppila score together compared to the ones for SEVR or Kauppila score alone. Conclusion: A quantitative analysis of vascular calcifications should be associated to a qualitative evaluation of arterial damage to better estimate cardiovascular mortality risk of ESRD patients. Further studies are needed to verify our hypothesis.
Keywords: Cardiovascular mortality